2019
DOI: 10.1038/s41534-019-0183-6
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of error-tradeoff uncertainty relation using a continuous-variable entangled state

Abstract: Heisenberg's original uncertainty relation is related to measurement effect, which is different from the preparation uncertainty relation. However, it has been shown that Heisenberg's errordisturbance uncertainty relation can be violated in some cases. We experimentally test the errortradeoff uncertainty relation by using a continuous-variable Einstein-Podolsky-Rosen (EPR) entangled state. Based on the quantum correlation between the two entangled optical beams, the errors on amplitude and phase quadratures of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…The rest two equations, Eqs. ( 27) and (28), are essential for understanding the performance of X ν , Y 2 ν , Y 0 ν and Z ν . From Eq.…”
Section: Probability Distributions and Families Of Posterior Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…The rest two equations, Eqs. ( 27) and (28), are essential for understanding the performance of X ν , Y 2 ν , Y 0 ν and Z ν . From Eq.…”
Section: Probability Distributions and Families Of Posterior Statesmentioning
confidence: 99%
“…Above all, the theory of uncertainty relations [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19], the central topic of the paper, has advanced dramatically in the last two decades. Experimental tests of uncertainty relations [20][21][22][23][24][25][26][27][28][29] also have been performed due to the rapid improvement of experimental techniques in recent years. In the paper, we present linear simultaneous measurements of position and momentum with minimum error-trade-off in each minimum uncertainty state.…”
Section: Introductionmentioning
confidence: 99%
“…Gaussian states, such as the squeezed state and the Einstein-Podolsky-Rosen (EPR) entangled state, play essential roles in continu-ous variable (CV) quantum information [29][30][31], where Gaussian states are generated deterministically and information is encoded in the position or momentum quadrature of photonic harmonic oscillators. For example, Gaussian states has been applied in quantum computation [32,33], quantum key distribution [34][35][36], quantum teleportation [37,38], quantum entanglement swapping [39][40][41], quantum dense coding [42,43], and verification of the error-disturbance uncertainty relation [44,45]. Recently, it has been shown that quantum coherence with infinite-dimensional systems can be quantified by relative entropy [46].…”
Section: Introductionmentioning
confidence: 99%
“…All of these experiments are in discrete-variable systems. Until recently, the test of the error-tradeoff uncertainty relation with continuous variables is experimentally demonstrated by using an Einstein-Podolsky-Rosen (EPR) entangled state [35].…”
Section: Introductionmentioning
confidence: 99%